Healthy herbal particle art coating

By adding herbal particles and negative ion adsorption components to artistic paints, the shortcomings of existing paints in formaldehyde purification and antibacterial control are solved, and the effects of air purification and long-term antibacterial control are achieved, and the environmental protection performance of the paint is improved.

CN119752259AInactive Publication Date: 2025-04-04GUANGXI ACAD OF SCI +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510057696.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing artistic paints lack effective purification functions in removing formaldehyde produced by interior decoration, and have insufficient antibacterial properties on bacteria.

Method used

Use a healthy herbal art paint containing water-based polyurethane, acrylic emulsion, herbal particles and negative ion adsorption components. The negative ion adsorption components are made of chitosan sustained release material, negative ion powder and modified activated carbon. They are produced by cross-linking reactions and have good air purification and antibacterial properties.

Benefits of technology

By adding herbal particles and negative ion adsorption components, the paint not only shows a three-dimensional embossing effect on the coating surface, but also effectively purifies indoor air, reduces formaldehyde concentration, and has long-term antibacterial properties, improving the environmental protection performance of the paint.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005241909370000072
    Figure BDA0005241909370000072
  • Figure BDA0005241909370000081
    Figure BDA0005241909370000081
Patent Text Reader

Abstract

The invention relates to a healthy herbal particle art coating. The healthy herbal particle art coating is prepared from components in parts by mass as follows: 40-60 parts of waterborne polyurethane, 80-100 parts of an acrylic emulsion, 10-22 parts of herbal particles, 8-12 parts of a negative ion adsorption component and 12-16 parts of diatomite, the negative ion adsorption component comprises a chitosan slow-release material, negative ion powder and modified activated carbon. The beautiful effect of the formed coating can be improved, and meanwhile, the green and healthy effects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coatings, and in particular to a healthy herbal particle art coating. Background Art

[0002] During the decoration process of indoor furniture, new furniture usually contains formaldehyde. Inhaling too much formaldehyde may cause headaches, fatigue and other phenomena. Therefore, after the new decoration, people usually choose to open windows for ventilation to remove formaldehyde. However, the removal speed of formaldehyde only through ventilation is slow.

[0003] Artistic paint is a new type of wall decoration art material. Artistic paint can be painted with various textures to achieve wallpaper-like decoration. However, the functions of artistic paints currently on the market are relatively simple. When used for home decoration, it does not have the effect of purifying the formaldehyde generated by decoration. Summary of the invention

[0004] In order to improve the environmental performance of the coating, the present application provides a healthy herbal particle art coating.

[0005] The healthy herbal grain art paint provided in this application adopts the following technical solution: A healthy herbal grain art paint comprises the following components in parts by weight: 40-60 parts of waterborne polyurethane, 80-100 parts of acrylic emulsion, 10-22 parts of herbal particles, 8-12 parts of negative ion adsorption components, and 12-16 parts of diatomaceous earth; The negative ion adsorption component comprises chitosan slow-release material, negative ion powder and modified activated carbon.

[0006] By adopting the above technical scheme, herbal particles are added to the paint in this application. After the paint is applied, the coating surface will have a three-dimensional relief effect. The herbal particles have good adsorption effect and can purify the indoor air. At the same time, the herbal particles have good antibacterial properties to avoid the growth of bacteria; a negative ion adsorption component is also added to the paint, and the negative ion adsorption component prepared by chitosan sustained-release material, negative ion powder and modified activated carbon also has a good air purification effect; chitosan is a natural polymer material, and its molecular structure contains rich functional groups such as amino and carboxyl groups, has good adsorption properties, and is green and environmentally friendly; activated carbon has stable chemical properties and toughness, and has a large specific surface area and rich pore structure, which can provide sufficient points for the adsorbate; negative ion powder can continuously release negative oxygen ions, which can improve people's health, and harmful suspended matter such as dust, haze, and particles in the air can combine with negative oxygen ions, thereby purifying the air, further improving the environmental protection performance of the paint.

[0007] Preferably, the negative ion adsorption component is prepared by the following method: The modified activated carbon, chitosan sustained-release material and negative ion powder are mixed, added into water and stirred to be evenly dispersed, and then glutaraldehyde is added, the temperature is raised to react, the solid is washed after the reaction, and the negative ion adsorption component is obtained after drying for 8 hours and grinding.

[0008] By adopting the above technical scheme, using activated carbon, chitosan sustained-release material and negative ions as raw materials and glutaraldehyde as a cross-linking agent, the modified activated carbon, chitosan sustained-release material and negative ion powder are cross-linked to generate negative ion adsorption components, which can adsorb harmful particles such as formaldehyde in the air, thereby promoting the purification effect of indoor air.

[0009] Preferably, the modified activated carbon comprises manganese dioxide and activated carbon.

[0010] By adopting the above technical solution, manganese dioxide is a stable metal oxide that can adsorb volatile organic compounds in the air and has good adsorption properties. Loading manganese dioxide on activated carbon can increase the adsorption performance of activated carbon. At the same time, it can catalyze the decomposition of harmful substances into harmless carbon dioxide and water, further improving the green and environmental performance of the coating.

[0011] Preferably, the modified activated carbon is prepared by the following method: The activated carbon is mixed with potassium permanganate solution, filtered after impregnation, and dried to obtain modified activated carbon.

[0012] Preferably, in the potassium permanganate solution, the concentration of potassium permanganate is 0.07-0.08 mol / L.

[0013] By adopting the above technical solution, preferably the concentration of potassium permanganate is within the above range, the stability of the prepared modified activated carbon can be further improved.

[0014] Preferably, the mass ratio of the modified activated carbon, chitosan sustained-release material and negative ion powder is (4.2-4.6):1.6:1.

[0015] By adopting the above technical solution, the mass ratio of the modified activated carbon, the chitosan sustained-release material and the negative ion powder is preferably within the above range, which can further improve the overall stability of the prepared negative ion adsorption component.

[0016] Preferably, the chitosan sustained-release material comprises whey protein, chitosan, sodium alginate and eugenol.

[0017] By adopting the above technical scheme, chitosan has good film-forming and antibacterial properties, and eugenol is a plant essential oil with good antioxidant and antibacterial properties. However, the phenolic structure of eugenol is easily and quickly inactivated, thereby losing its antibacterial and antioxidant properties. Eugenol is coated with whey protein, sodium alginate and chitosan to form a microcapsule structure, so that eugenol can be slowly released, thereby making the prepared artistic coating have a long-lasting antibacterial effect. At the same time, the antioxidant property of the herbal particles can be improved, thereby further enhancing the long-term antibacterial and adsorption properties of the herbal particles and improving the green environmental protection performance of the artistic coating.

[0018] Preferably, the chitosan sustained-release material is prepared in the following manner: Chitosan is mixed with acetic acid solution, and stirred until chitosan is completely dissolved to obtain a chitosan solution; whey protein is mixed with water, and stirred until whey protein is completely dissolved, and then an emulsifier is added, and then eugenol is added, and stirred to obtain a mixed solution; the mixed solution is added to the chitosan solution, and ultrasonicated after stirring; sodium sulfate aqueous solution is added after ultrasonication, and ultrasonication is continued. After centrifugation, the upper liquid is removed, and the precipitate is washed to obtain eugenol-loaded chitosan microcapsules; sodium alginate is mixed with water, and stirred to obtain a sodium alginate solution, and eugenol-loaded chitosan microcapsules are added to the sodium alginate solution, stirred and centrifuged, and then transferred to a calcium chloride aqueous solution, and continued to centrifuge to obtain a solid precipitate, which is washed and freeze-dried to obtain a chitosan sustained-release material.

[0019] By adopting the above technical scheme, the complex generated by the electrostatic effect between protein and polysaccharide can effectively improve the embedding effect of the core material eugenol and further improve the stability of eugenol. At the same time, the microcapsules prepared with whey protein, chitosan and sodium alginate can not only improve the embedding rate of eugenol, but also provide a physical barrier to further improve the stability of eugenol. Therefore, the stability and mechanical strength of the prepared chitosan sustained-release material are further improved, and the artistic coating has long-lasting antibacterial properties.

[0020] Preferably, the mass ratio of the whey protein, chitosan, sodium alginate and eugenol is (0.2:0.5)-0.7:0.6:1.

[0021] By adopting the above technical solution, the mass ratio of whey protein, chitosan, sodium alginate and eugenol is preferably within the above range, which can further improve the overall stability of the prepared chitosan sustained-release material.

[0022] Preferably, the herbal particles include any one of rosemary particles, thyme particles, and motherwort particles, or a mixture of two or more thereof.

[0023] In summary, the present application includes at least one of the following beneficial technical effects: 1. The present application adds herbal particles to the coating, which have good adsorption properties and can purify indoor air. At the same time, the herbal particles have good antibacterial properties and can prevent the growth of bacteria. After the artistic coating is applied, due to the large particle size of the herbal particles, a three-dimensional relief effect can be reflected on the coating surface, playing a dual role of health and beauty; a negative ion adsorption component is also added to the coating, and the negative ion adsorption component prepared by chitosan sustained-release material, negative ion powder and modified activated carbon has a good air purification effect. After the three are cross-linked and compounded, they can synergistically adsorb gases in the indoor air and play a synergistic antibacterial role, further improving the overall antioxidant and antibacterial properties of the coating; 2. After manganese dioxide is loaded on activated carbon, the surface of the composite material is loaded with particles of different sizes and shapes, and they are piled up into a larger three-dimensional structure. The modified activated carbon is more conducive to the adsorption and decomposition of harmful gases in the air, thereby promoting the improvement of the adsorption performance of the coating; 3. Chitosan sustained-release material is prepared by sodium alginate, chitosan and eugenol. Eugenol has good antioxidant properties. After chitosan and sodium alginate are used as wall materials to coat eugenol, eugenol can be slowly released, thereby playing a long-term antibacterial and antioxidant role, thereby improving the long-term antibacterial properties of artistic coatings. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments: Raw materials description: All raw materials in the examples can be obtained from commercial sources.

[0025] Example 1 Preparation of chitosan sustained-release material: 3.26 g of chitosan (CAS No.: 9012-76-4) was mixed with 60 g of 1% acetic acid solution, and stirred for 3 h until the chitosan was completely dissolved to obtain a chitosan solution. 1.31 g of whey protein (CAS No.: 84082-51-9) was mixed with 30 g of deionized water, and stirred for 30 min until the whey protein was completely dissolved. Then, an equal volume fraction of emulsifier Span-80 (CAS No.: 1338-43-8) was added, and then 6.52 g of eugenol (CAS No.: 97-53-0) was added. After stirring for 2 h, a mixed solution was obtained. The mixed solution was added to the chitosan solution, and ultrasonicated after stirring. After ultrasonication, 10 mL of 1.2% sodium sulfate solution was added. solution, continue ultrasonication for 10 minutes, remove the upper liquid after centrifugation, wash the precipitate with deionized water to obtain eugenol-loaded chitosan microcapsules; mix 3.91g of sodium alginate (CAS No.: 9005-38-3) with 30g of deionized water, stir to obtain a sodium alginate solution, add eugenol-loaded chitosan microcapsules to the sodium alginate solution, stir for 10 minutes, centrifuge at 3000r / min for 5 minutes, then transfer to a calcium chloride aqueous solution, continue to centrifuge at 3000r / min for 5 minutes to obtain a solid precipitate, finally wash 3 times with a Span-80 solution containing 1% volume fraction, and freeze-dry at -20°C for 12 hours to obtain a chitosan sustained-release material.

[0026] Preparation of modified activated carbon: 30 g of activated carbon was added into 300 mL of potassium permanganate solution, immersed for 12 h, filtered and dried to obtain modified activated carbon, wherein the concentration of potassium permanganate in the potassium permanganate solution was 0.07 mol / L.

[0027] Preparation of negative ion adsorption components: 18.53 g of modified activated carbon, 7.06 g of chitosan sustained-release material, and 4.41 g of negative ion powder were mixed, added to 500 g of deionized water, stirred and evenly dispersed, and then 18 mL of glutaraldehyde (CAS No.: 111-30-8) was added, and the mixture was reacted at 40°C for 6 h. After the reaction, the excess reactants were washed with deionized water, and the solid residue was placed in an oven at 60°C, dried for 8 h, and ground to obtain the negative ion adsorption component.

[0028] Preparation of healthy herbal grain art paint: 40 g of waterborne polyurethane, 80 g of acrylic emulsion, 12 g of diatomaceous earth, 10 g of herbal particles and 8 g of negative ion adsorption component were mixed and stirred to obtain healthy herbal particle art paint.

[0029] The herbal granules are rosemary granules.

[0030] Example 2 Preparation of chitosan sustained-release material: 4.2 g of chitosan was mixed with 60 g of 1% acetic acid solution, and stirred for 3 h until the chitosan was completely dissolved to obtain a chitosan solution; 1.2 g of whey protein was mixed with 30 g of deionized water, and stirred for 30 min until the whey protein was completely dissolved, and then an equal volume fraction of emulsifier Span-80 was added, and then 6 g of eugenol was added, and stirred for 2 h to obtain a mixed solution, which was added to the chitosan solution, stirred and then ultrasonicated, and 10 mL of 1.2% sodium sulfate aqueous solution was added after ultrasonication, and ultrasonication was continued for 10 min. The upper liquid was removed after centrifugation, and the mixture was removed by using a deionized water. The precipitate was washed with deionized water to obtain eugenol-loaded chitosan microcapsules; 3.6 g of sodium alginate was mixed with 30 g of deionized water, and the mixture was stirred to obtain a sodium alginate solution; the eugenol-loaded chitosan microcapsules were added to the sodium alginate solution, and the mixture was stirred for 10 min, and then centrifuged at 3000 r / min for 5 min, and then transferred to a calcium chloride aqueous solution, and centrifuged at 3000 r / min for 5 min to obtain a solid precipitate, and finally washed three times with a 1% volume fraction of Span-80 solution, and freeze-dried at -20°C for 12 h to obtain a chitosan sustained-release material.

[0031] Preparation of modified activated carbon: 30 g of activated carbon was added into 300 mL of potassium permanganate solution, immersed for 12 h, filtered and dried to obtain modified activated carbon, wherein the concentration of potassium permanganate in the potassium permanganate solution was 0.08 mol / L.

[0032] Preparation of negative ion adsorption components: 19.16 g of modified activated carbon, 6.67 g of chitosan sustained-release material, and 4.17 g of negative ion powder were mixed, added to 500 g of deionized water, stirred and evenly dispersed, and then 18 mL of glutaraldehyde was added. The mixture was reacted at 40 ° C for 6 h. After the reaction, the excess reactants were washed with deionized water. The solid filter residue was placed in an oven at 60 ° C, dried for 8 h, and ground to obtain the negative ion adsorption component.

[0033] Preparation of healthy herbal grain art paint: 60 g of waterborne polyurethane, 100 g of acrylic emulsion, 16 g of diatomaceous earth, 22 g of herbal particles and 12 g of negative ion adsorption components were mixed and stirred to obtain healthy herbal particle art paint.

[0034] The herbal granules are thyme granules.

[0035] Example 3 Preparation of chitosan sustained-release material: 3.75 g of chitosan was mixed with 60 g of 1% acetic acid solution, and stirred for 3 h until the chitosan was completely dissolved to obtain a chitosan solution. 1.25 g of whey protein was mixed with 30 g of deionized water, and stirred for 30 min until the whey protein was completely dissolved. Then, an equal volume fraction of emulsifier Span-80 was added, and then 6.25 g of eugenol was added. After stirring for 2 h, a mixed solution was obtained. The mixed solution was added to the chitosan solution, and ultrasonicated after stirring. After ultrasonication, 10 mL of 1.2% sodium sulfate aqueous solution was added, and ultrasonication was continued for 10 min. The upper layer of liquid was removed after centrifugation. The precipitate was washed with deionized water to obtain eugenol-loaded chitosan microcapsules; 3.75 g of sodium alginate was mixed with 30 g of deionized water, and the mixture was stirred to obtain a sodium alginate solution; the eugenol-loaded chitosan microcapsules were added to the sodium alginate solution, and the mixture was stirred for 10 min, and then centrifuged at 3000 r / min for 5 min, and then transferred to a calcium chloride aqueous solution, and centrifuged at 3000 r / min for 5 min to obtain a solid precipitate; finally, the solid precipitate was washed three times with a 1% volume fraction of Span-80 solution, and freeze-dried at -20°C for 12 h to obtain a chitosan sustained-release material.

[0036] Preparation of modified activated carbon: 30 g of activated carbon was added into 300 mL of potassium permanganate solution, immersed for 12 h, filtered and dried to obtain modified activated carbon, wherein the concentration of potassium permanganate in the potassium permanganate solution was 0.075 mol / L.

[0037] Preparation of negative ion adsorption components: 18.85 g of modified activated carbon, 6.86 g of chitosan sustained-release material, and 4.29 g of negative ion powder were mixed, added to 500 g of deionized water, stirred and evenly dispersed, and then 18 mL of glutaraldehyde was added. The mixture was reacted at 40 ° C for 6 h. After the reaction, the excess reactants were washed with deionized water. The solid filter residue was placed in an oven at 60 ° C, dried for 8 h, and ground to obtain the negative ion adsorption component.

[0038] Preparation of healthy herbal grain art paint: 50 g of waterborne polyurethane, 90 g of acrylic emulsion, 14 g of diatomaceous earth, 16 g of herbal particles and 10 g of negative ion adsorption components were mixed and stirred to obtain healthy herbal particle art paint.

[0039] The herbal granules are prepared by mixing the herb granules, thyme granules and motherwort granules.

[0040] Example 4 Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that when preparing modified activated carbon, the concentration of potassium permanganate in the potassium permanganate solution is 0.05 mol / L.

[0041] Example 5 Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that when preparing modified activated carbon, the concentration of potassium permanganate in the potassium permanganate solution is 0.1 mol / L.

[0042] Example 6 Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that when preparing the chitosan sustained-release material, 1.43 g of whey protein, 2.14 g of chitosan, 4.29 g of sodium alginate and 7.14 g of eugenol are used.

[0043] Example 7 Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that when preparing the chitosan sustained-release material, 1.11 g of whey protein, 5 g of chitosan, 3.33 g of sodium alginate and 5.56 g of eugenol are used.

[0044] Example 8 Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that when preparing the chitosan sustained-release material, whey protein is replaced by chitosan.

[0045] Example 9 Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that when preparing the negative ion adsorption component, 17.81 g of modified activated carbon, 7.5 g of chitosan sustained-release material, and 4.69 g of negative ion powder are used.

[0046] Example 10 Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that when preparing the negative ion adsorption component, 19.73 g of modified activated carbon, 6.32 g of chitosan sustained-release material, and 3.95 g of negative ion powder are used.

[0047] Embodiment 11 Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that when preparing the negative ion adsorption component, the modified activated carbon is replaced by ordinary activated carbon.

[0048] Example 12 Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that when preparing the negative ion adsorption component, the chitosan sustained-release material replaces chitosan.

[0049] Comparative Example 1 Comparative Example 1 is based on Example 3, and in Comparative Example 1, the negative ion adsorption component is replaced by ordinary negative ion powder.

[0050] Comparative Example 2 Comparative Example 2 is based on Example 3, and in Comparative Example 2, the chitosan sustained-release material is replaced with eugenol.

[0051] The following performance tests were performed on the samples of Examples 1-12 and Comparative Examples 1-2: (1) Antibacterial performance test Based on GB / T 1741-2007 Determination of Antibacterial Properties of Coatings, the antibacterial properties of each embodiment and comparative example were tested for 3 days and 28 days, and the results were filled in Table 1.

[0052] (2) Formaldehyde adsorption test Take 0.5 g of the prepared sample from each example and comparative example, spread it flat on a surface dish, and adjust the formaldehyde concentration in the test box to 1.0-2.0 mg / m 3 , place the dispersed samples in the test box and start timing, record the formaldehyde concentration at certain intervals, stop the test when the formaldehyde concentration in the closed container is basically stable, record the average formaldehyde concentration, test each sample 3 times, take the average value, and fill in the test results in Table 1; Formaldehyde removal rate Where C0 is the initial formaldehyde concentration (mg / cm 3 ), Ce is the concentration of formaldehyde at equilibrium (mg / cm 3 ) Table 1 Performance test results of Examples 1-12 and Comparative Examples 1-2 Combined with Table 1, it can be seen that the 3d Escherichia coli antibacterial rate and the Staphylococcus aureus antibacterial rate of Examples 1-3 are both 99.5% and above, indicating that the herbal granule art paint prepared in the present application has good antibacterial properties, and the 28d Escherichia coli antibacterial rate and the Staphylococcus aureus antibacterial rate of Examples 1-3 are both 96% and above, indicating that the herbal granule art paint prepared in the present application has long-term antibacterial properties; the formaldehyde removal rate of Examples 1-3 is 96% and above, indicating that the herbal granule art paint prepared in the present application has good formaldehyde adsorption performance.

[0053] In Example 4 and Example 5, when preparing modified activated carbon, the concentration of potassium permanganate in the potassium permanganate solution is not within the range specified in the present application. When the concentration of potassium permanganate is too low, the content of manganese dioxide attached to the surface of the activated carbon decreases, and it is difficult to further promote the oxidative decomposition effect of formaldehyde, thereby affecting the adsorption and removal performance of formaldehyde. After the content of manganese dioxide decreases, the antibacterial performance is also affected to a certain extent; when the concentration of potassium permanganate is too high, the content of manganese dioxide generated on the surface of the activated carbon is too high, which blocks a large number of microporous structures on the surface of the activated carbon, affects the adsorption performance of formaldehyde, and the antibacterial performance is also reduced. Therefore, the antibacterial performance and formaldehyde adsorption performance of Example 4 and Example 5 are both reduced.

[0054] In Example 6 and Example 7, when preparing chitosan sustained-release materials, the mass ratios of whey protein, chitosan, sodium alginate and eugenol are not within the range specified in the present application. When the chitosan content is too much, the viscosity of the chitosan sustained-release material system is too large, which is not conducive to the stirring and combining of eugenol with the system, thereby reducing the dispersibility of eugenol, and reducing the stability of the prepared chitosan sustained-release material. The reduced sustained-release performance of eugenol affects the overall antibacterial performance of the system, and also affects the binding stability between the prepared chitosan sustained-release material and the negative ion powder and modified limestone. When the chitosan content decreases, the ability to disperse the oil phase decreases, and the loading rate of eugenol decreases. Therefore, the antibacterial performance of the prepared chitosan sustained-release material decreases, so the performance of Example 6 and Example 7 both decreases.

[0055] In Example 8, when preparing chitosan sustained-release material, whey protein was replaced with chitosan, and only chitosan was used to coat eugenol, which made it difficult to further increase the loading amount of eugenol, thus affecting the content of eugenol. Therefore, the performance of the examples was reduced.

[0056] In the preparation of negative ion adsorption components in Examples 9 and 10, the mass ratios of modified activated carbon, chitosan sustained-release material and negative ion powder are not within the range specified in the present application. When the content of modified activated carbon is too little, the content of manganese dioxide loaded on the surface of the activated carbon also decreases, which affects the adsorption and decomposition performance of formaldehyde in indoor gas. When the content of activated carbon is too much, the overall stability of the prepared negative ion adsorption component is affected. Therefore, the performance of Examples 9 and 10 are both reduced.

[0057] In Example 11, when preparing the negative ion adsorption component, the modified activated carbon is replaced with ordinary activated carbon. Using only ordinary activated carbon, activated carbon without manganese dioxide loading is difficult to catalyze the decomposition of formaldehyde. At the same time, it is difficult to further promote the adsorption performance of the activated carbon, and the pore structure on the surface of the activated carbon is also difficult to improve, and the antibacterial performance is also reduced. Therefore, the formaldehyde adsorption performance and antibacterial performance of Example 11 are both reduced.

[0058] In Example 12, when preparing the negative ion adsorption component, the chitosan sustained-release material was replaced with ordinary chitosan. Ordinary chitosan does not have eugenol added, and it is difficult to further exert antibacterial properties, and it is also impossible to further improve the sustained-release antibacterial properties of the system. The antioxidant properties are also affected, and the overall stability of the system is also reduced. Therefore, the antibacterial properties and formaldehyde adsorption properties of Example 12 are both reduced.

[0059] In Comparative Example 1, the negative ion adsorption component is replaced with ordinary negative ion powder. It is difficult to further improve the air purification performance by only releasing negative oxygen ions through the negative ion powder to purify the air, and the adsorption effect on harmful gases is also reduced, and the antibacterial performance is difficult to further improve. Therefore, the antibacterial performance and formaldehyde adsorption performance of Comparative Example 1 are both reduced.

[0060] In Comparative Example 2, the chitosan sustained-release material is replaced with eugenol. The eugenol that is not coated will be quickly deactivated and it is difficult to exert long-term antibacterial properties. In addition, the antibacterial properties of the system without adding chitosan are difficult to be further improved. The overall mechanical properties of the system are reduced, and the adsorption performance for formaldehyde is also reduced. Therefore, all performances of Comparative Example 2 are reduced.

[0061] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of ​​the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A healthy herbal grain art paint, characterized by: The composition comprises the following components in parts by weight: 40-60 parts of waterborne polyurethane, 80-100 parts of acrylic emulsion, 10-22 parts of herbal particles, 8-12 parts of negative ion adsorption components, and 12-16 parts of diatomaceous earth; The negative ion adsorption component comprises chitosan slow-release material, negative ion powder and modified activated carbon.

2. The healthy herbal grain art paint according to claim 1, characterized in that: The negative ion adsorption component is prepared by the following method: The modified activated carbon, chitosan sustained-release material and negative ion powder are mixed, added into water and stirred to be evenly dispersed, and then glutaraldehyde is added, the temperature is raised to react, the solid is washed after the reaction, and the negative ion adsorption component is obtained after drying for 8 hours and grinding.

3. The healthy herbal grain art paint according to claim 1, characterized in that: The modified activated carbon comprises manganese dioxide and activated carbon.

4. The healthy herbal grain art paint according to claim 3, characterized in that: The modified activated carbon is prepared by the following method: The activated carbon is mixed with potassium permanganate solution, filtered after impregnation, and dried to obtain modified activated carbon.

5. The healthy herbal grain art paint according to claim 4, characterized in that: In the potassium permanganate solution, the concentration of potassium permanganate is 0.07-0.08 mol / L.

6. The healthy herbal grain art paint according to claim 1, characterized in that: The mass ratio of the modified activated carbon, the chitosan sustained-release material and the negative ion powder is (4.2-4.6):1.6:

1.

7. The healthy herbal grain art paint according to claim 1, characterized in that: The chitosan sustained-release material comprises whey protein, chitosan, sodium alginate and eugenol.

8. The healthy herbal grain art paint according to claim 7, characterized in that: The chitosan sustained-release material is prepared in the following manner: Chitosan is mixed with acetic acid solution, and stirred until chitosan is completely dissolved to obtain a chitosan solution; whey protein is mixed with water, and stirred until whey protein is completely dissolved, and then an emulsifier is added, and then eugenol is added, and stirred to obtain a mixed solution; the mixed solution is added to the chitosan solution, and ultrasonicated after stirring; sodium sulfate aqueous solution is added after ultrasonication, and ultrasonication is continued. After centrifugation, the upper liquid is removed, and the precipitate is washed to obtain eugenol-loaded chitosan microcapsules; sodium alginate is mixed with water, and stirred to obtain a sodium alginate solution, and eugenol-loaded chitosan microcapsules are added to the sodium alginate solution, stirred and centrifuged, and then transferred to a calcium chloride aqueous solution, and continued to centrifuge to obtain a solid precipitate, which is washed and freeze-dried to obtain a chitosan sustained-release material.

9. The healthy herbal grain art paint according to claim 8, characterized in that: The mass ratio of the whey protein, chitosan, sodium alginate and eugenol is (0.2:0.5)-0.7:0.6:

1.

10. The healthy herbal grain art paint according to claim 1, characterized in that: The herbal granules include any one of rosemary granules, thyme granules, and motherwort granules, or a mixture of two or more of the above.

Citation Information

Patent Citations

  • Active carbon coating powder having air-purifying function

    CN105272053A

  • Anti-tear environment-friendly water-based paint

    CN106085063A

  • High-performance formaldehyde adsorbent and preparation method thereof

    CN108745293A

  • Formaldehyde removal paint special for kindergarten furniture and preparing method of paint

    CN109971278A

  • Method for storing cattle and sheep carcasses through edible controlled-release film spraying and film spraying equipment

    CN115320918A